Privacy Protection of Public Figures in China—The Case of Yundi Li’s Prostitution - Yanbing Wang (Studies in Law and Justice, 2023)
Since the birth of the right to privacy, more and more attention has been paid to the protection of the right to privacy. In China, since the introduction of privacy rights from the West, the protection of privacy rights has been focused on civil law, while the protection of privacy rights in legislation and judicial practice in other branches of law has only been superficial but not in-depth. The effect of civil law on the protection of privacy rights is undeniable, especially after the introduction of the Civil Code, which provides more thorough and complete regulations on privacy rights in the field of civil law. However, with the development of society, relying on civil law alone to protect the right to privacy has become a challenge. The protection of the right to privacy of public figures is even more lacking. For example, the case of Li Yundi’s prostitution, which was publicly reported by the Beijing Chaoyang Public Security Bureau on 21 October 2021, reveals the loopholes in the protection of privacy and the privacy of public figures in China. Firstly, civil law in China has been effective in protecting the right to privacy, but in this case, the right of public security to disclose Li Yundi’s private life involves the infringement of citizens’ privacy by public power. Secondly, in China, public figures are often involved in the public interest, and it is the consensus of the academia and society as a whole that anyone in conflict with the public interest should give way to the public interest. However, in judicial practice, the author believes that it is unfair to treat public figures and ordinary citizens differently in terms of privacy rights when the public interest is not seriously endangered. Therefore, this article aims to analyse the current status and shortcomings of the legislation and judicial practice on the protection of the privacy of public figures in China on the basis of the right to privacy and the privacy of public figures, and to draw on the advanced experience of other countries in order to establish and improve the privacy protection mechanism of public figures in China.